The Pythagorean golden verses : with introduction and commentary - Thom, Johan Carl, 1954- (Religions in the Graeco-Roman World, 1995)
This book is a commentary on the Pythagorean Golden Verses , a neglected, but once very popular poem of the Hellenistic period. The goal of the poem is to introduce its readers to the basic moral, religious and philosophical doctrines of the Pythagorean sect and to guide them to spiritual maturity. The first part of the book treats still unresolved introductory matters such as the date, authorship, genre, composition, and the historical locus of the poem. This is followed by a text with translation on facing pages, and a detailed commentary containing a wealth of comparative material from the Greco-Roman period, including early Christianity and Judaism. Particularly valuable are the extensive discussions of the moral topoi and religious themes encountered in the poem.